ANALISA TINGKAT KEBISINGAN TERHADAP PEKERJA PADA PROSES PRODUKSI INDUSTRI SEMEN - Riswanda Putri Andini; Mohammad Mirwan (EnviroUS, 2021)
The cement industry in the new research plant was established for ± 5 years. The existence of this establishment certainly has negative impacts, one of which is the production of high-intensity / noisy sound. The noise in the cement industry comes from the cement production process where raw materials are processed into finished materials that are ready to be distributed to consumers. The noise will certainly have an impact on the surrounding workers. This study aims to show the very poor intensity of the processes that occur and to see the relationships that occur in communication, psychology, and worker physiology. The highest noise occurs in the raw factory area with a distance of 5 meters from the equipment where the intensity is 93.23 dB. Based on the Regulation of the Minister of Manpower of the Republic of Indonesia No. 5 of 2018, this exceeds the allowable threshold value of 85 dB with an exposure time of 8 hours. And responsive from workers who do not feel disturbed by what happened.